Readability of Narrative Disclosures in 10-K Reports: Does Managerial Ability Matter? - Hasan, Mostafa (Routledge Journals, 2018)
© 2018, © 2018 European Accounting Association. This study examines the association between managerial ability and the readability of narrative disclosures in 10-K reports. Using a large US sample from 1994 to 2015, we find that managerial ability is significantly positively associated with the readability of narrative disclosures in 10-K reports. We also find that this association is more pronounced for firms with high levels of profitability. In addition, firms’ financial performance mediates the association between managerial ability and the readability of 10-K reports. Further analysis shows that the association was more pronounced before the implementation of the plain English disclosure rules. These results are robust to alternative specifications of managerial ability, 10-K report readability, and the endogeneity concern. Overall, findings from this study suggest that managerial ability matters for improving the readability of corporate disclosures.